2021
DOI: 10.1097/ede.0000000000001343
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Hypertensive Disorders During Pregnancy: ICD-10 Codes in a High-burden Southeastern United States Hospital

Abstract: Background: Identification of hypertensive disorders in pregnancy research often uses hospital International Classification of Diseases v. 10 (ICD-10) codes meant for billing purposes, which may introduce misclassification error relative to medical records. We estimated the validity of ICD-10 codes for hypertensive disorders during pregnancy overall and by subdiagnosis, compared with medical record diagnosis, in a Southeastern United States high disease burden hospital. Methods: We linked medical record data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…This is likely due to the intended function of ICD codes being for billing, not diagnostic purposes 51 . Specifically, previous studies have shown that using ICD codes alone to identify preeclampsia patients performed poorly when compared to the gold standard of chart review 52 , 53 . Indeed, to identify as many PE cases as possible, ICD codes should be combined with EMR records (such as vitals and laboratory results).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the intended function of ICD codes being for billing, not diagnostic purposes 51 . Specifically, previous studies have shown that using ICD codes alone to identify preeclampsia patients performed poorly when compared to the gold standard of chart review 52 , 53 . Indeed, to identify as many PE cases as possible, ICD codes should be combined with EMR records (such as vitals and laboratory results).…”
Section: Discussionmentioning
confidence: 99%
“…There is also recent research suggesting that the ICD-10 codes for pre-eclampsia without severe features had low sensitivity. 23 Other studies have demonstrated high validity of Medicaid data in research. 24 In this analysis, we have no data to validate diagnoses and rely on the accuracy of the claims.…”
Section: Discussionmentioning
confidence: 98%
“…This probably underestimated the validity of the data as they only used one hospital’s data records for cross-checking. There is also recent research suggesting that the ICD-10 codes for pre-eclampsia without severe features had low sensitivity 23. Other studies have demonstrated high validity of Medicaid data in research 24.…”
Section: Discussionmentioning
confidence: 99%
“… 48 The definitions of GHTD based on ICD codes have also been shown to be valid. 49 We did not have enough power to examine the subtypes of GHTD (preeclampsia/eclampsia and gestational hypertension) individually. We used a composite cardiovascular outcome, which limits our ability to understand the associations of GD and/or GHTD with specific individual cardiovascular outcomes, and thus which outcome may drive the observed association.…”
Section: Discussionmentioning
confidence: 99%